Open-Access Metabolomics Databases for Natural Product Research: Present Capabilities and Future Potential - Johnson, Sean R.; Lange, Bernd Markus (Frontiers in Bioengineering and Biotechnology, 2015)
Various databases have been developed to aid in assigning structures to spectral peaks observed in metabolomics experiments. In this review article, we discuss the utility of currently available open-access spectral and chemical databases for natural products discovery. We also provide recommendations on how the research community can contribute to further improvements